The developmental changes in mitochondrial DNA content per cell in human cord blood leukocytes during gestation - Pejznochová, M; Tesařová, M; Honzík, T; Hansíková, H; Magner, M; Zeman, J (Physiological research, 2008)
The mitochondrial DNA (mtDNA) amount in cells as the basis for mitochondrial energy generating system, which produces ATP, plays an important role in the fetal development and postnatal morbidity. Isolated human cord blood leukocytes (HCBL) contribute very little to the overall metabolic turnover, but they may serve as easily available marker cells for the study of the mtDNA amount changes in cord blood during fetal development. The aim of our study was to analyze the mtDNA amount in HCBL. HCBL were isolated from cord blood samples of 107 neonates born between the 25th and 41st week of gestation. The mtDNA amount was analyzed by the real-time PCR method. The significant negative correlations were found between the relative mtDNA amount in HCBL and gestational age (r = -0.54, p<0.01) and birth weight (r = -0.43, p<0.01), respectively. The results revealed that the mtDNA content per cell decreases in HCBL with progressing fetal development. This may be explained by gradual shift of the hematopoiesis from fetal liver to bone marrow during the second half of pregnancy presumably accompanied by decreasing cell volume of HCBL as it was shown similarly in red blood cells.
Keywords: Reproducibility of Results; Leukocytes; reprodukovatelnost výsledků; těhotenství; polymerázová řetězová reakce; Polymerase Chain Reaction; down regulace; Gestational Age; Sensitivity and Specificity; mužské pohlaví; DNA, Mitochondrial; Fetal Blood; Down-Regulation; gestační stáří; Infant, Newborn; ženské pohlaví; novorozenec; Humans; Pregnancy; mitochondriální DNA; senzitivita a specificita; Birth Weight; porodní hmotnost; Female; leukocyty; fetální krev; lidé; Male